Principles of Legal Compliance on the Constitutional Court Decisions Adoption in Legislation - Rakia, A. Sakti R. S.; Muhammad Ali; Laode Muhammad Taufiq Afoeli; Wahab Aznul Hidaya; Seguito Monteiro (Jurnal Jurisprudence, 2024)
ABSTRACT Purpose: This study aims to analyze the compliance of the House of Representatives with the follow-up to the Constitutional Court Decision. Methodology: The research method used normative-juridical legal research. The method used the constitutional approach and the statutory approach. Results: The results of this study indicate that the Constitutional Court Decision is equivalent to the constitution itself; thus obedience to the decision of the constitutional court is absolute. Applications of this study: The purpose of this research is to contribute ideas about how every decision of the Constitutional Court can be adhered to with constitutional principles. Novelty/Orginality of this study: This research found that the Constitutional Court's decision should be deemed equivalent to the constitution. This research also contributes ideas so that constitutional obedience can be enforced in every act created as a result of a Constitutional Court decision. Keywords: Constitutional Court Decisions, Legislation, National Law Development, Legal Compliance Principles.   ABSTRAK  Tujuan: Penelitian ini bertujuan untuk menganalisis kepatuhan Dewan Perwakilan Rakyat terhadap tindak lanjut Putusan Mahkamah Konstitusi. Metodologi: Metode penelitian yang digunakan adalah penelitian hukum normatif-yuridis. Metode ini menggunakan pendekatan konstitusional dan pendekatan perundang-undangan. Hasil: Hasil penelitian ini menunjukkan bahwa Putusan Mahkamah Konstitusi setara dengan konstitusi itu sendiri, sehingga ketaatan terhadap putusan Mahkamah Konstitusi adalah mutlak. Aplikasi penelitian ini: Tujuan dari penelitian ini adalah untuk menyumbangkan gagasan tentang bagaimana setiap putusan Mahkamah Konstitusi dapat dipatuhi dengan prinsip-prinsip konstitusional. Kebaruan/Orisinalitas penelitian ini: Penelitian ini menemukan bahwa putusan Mahkamah Konstitusi harus dianggap setara dengan konstitusi. Penelitian ini juga menyumbangkan gagasan agar kepatuhan konstitusional dapat ditegakkan dalam setiap tindakan yang dibuat sebagai hasil dari putusan Mahkamah Konstitusi.  Kata kunci: Putusan Mahkamah Konstitusi, Perundang-undangan, Pengembangan Hukum Nasional, Prinsip-prinsip Kepatuhan Hukum